Legal protection of citizens' constitutional rights in the 2024 simultaneous elections - Didik Suhariyanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The 2024 Simultaneous Elections are a significant moment in Indonesia's democracy, focusing on citizens' constitutional rights, especially the right to vote and be elected. However, challenges such as issues with the accuracy of the Permanent Voter List (DPT), accessibility for vulnerable groups, and law enforcement against violations of voting rights remain critical. This study aims to analyze the legal protection of citizens' constitutional rights in the 2024 Simultaneous Elections, identify challenges in protecting these rights, and evaluate the role of election bodies like the General Elections Commission (KPU), the Election Supervisory Board (Bawaslu), and the Constitutional Court (MK). Using a qualitative approach and library research, this study reviews relevant literature, legislation, and reports from related institutions. The findings reveal that despite a clear legal framework, challenges persist, particularly concerning the DPT's accuracy, accessibility for vulnerable groups, and law enforcement. The role of election bodies like KPU, Bawaslu, and MK has not been fully effective in addressing these issues. The research concludes that further efforts are needed to improve the DPT system, enhance access for vulnerable groups, and strengthen law enforcement. The study emphasizes the importance of strengthening oversight, improving voter education, and optimizing technology to protect constitutional rights and ensure election integrity.